Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Jasa Service Pada PT. Astra International Tbk. – Daihatsu Malalayang - Angely, Gisyel; Tampi, Johny R. E.; Mukuan, Danny D. S. (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
The purpose of this study was to study the effect of service quality consisting of tangible, reliability, responsiveness, assurance, and empathy strengthening towards customer satisfaction. Regarding the problem in this study, whether the service quality offered to customer satisfaction services at PT. Astra International Tbk. - Daihatsu Malalayang. This type of research is quantitative research with descriptive research. The populations in this study were all service customers at PT. Astra International Tbk. - Daihatsu Malalayang, with a sample of 99 respondents. Technique analysis data uses multiple linear regression, t test, f test, and test coefficient of determination (R2). Based on the results of multiple linear regression analysis that includes simultaneous tangible, reliability, responsiveness, assurance, and empathy strengthen the service satisfaction of customers at PT. Astra International Tbk. - Daihatsu Malalayang by 54.0%. While the variables of reliability, responsiveness, and assurance are not partial to customer service satisfaction at PT. Astra International Tbk. - Daihatsu Malalayang. And the most dominant service quality variable is empathy.